2017
DOI: 10.2135/cropsci2016.05.0321
|View full text |Cite
|
Sign up to set email alerts
|

Seed Yield Components in Single Plants of Diverse Scandinavian Tetraploid Red Clover Populations (Trifolium pratense L.)

Abstract: R ed clover (Trifolium praTense L.) is one of the most widely grown forage legumes in temperate areas, together with alfalfa (Medicago sativa L.) and white clover (Trifolium repens L.) (Boller et al., 2010). Red clover is cultivated in mixtures with grasses on approximately four million hectares worldwide (Isobe et al., 2014). Red clover in grass mixtures is important because its nitrogen-fixing ability, through symbiosis with Rhizobium leguminosarum biovar trifolii, reduces the need for nitrogen (N) input in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…To conclude, recent studies have identified HN and SN/H as major determinants of seed yield in single plants and in dense stands of red clover [9,26,58,60,61]. Lower seed yield in tetraploids than in diploid genotypes is mostly explained by the lower seed number per head, and only partly by the lower number of ripe flower heads at seed harvest.…”
Section: Seed Yield Componentsmentioning
confidence: 88%
See 3 more Smart Citations
“…To conclude, recent studies have identified HN and SN/H as major determinants of seed yield in single plants and in dense stands of red clover [9,26,58,60,61]. Lower seed yield in tetraploids than in diploid genotypes is mostly explained by the lower seed number per head, and only partly by the lower number of ripe flower heads at seed harvest.…”
Section: Seed Yield Componentsmentioning
confidence: 88%
“…Recent studies at the genotype level have provided different insights. Three recent studies found that tetraploid genotypes indeed have longer CTL than diploids [26,60,61], but a very large overlap in CTL between ploidy levels was also found. In addition, the corolla tube diameter (CTD) is larger in tetraploids than in diploids [26].…”
Section: Inadequate Pollinationmentioning
confidence: 97%
See 2 more Smart Citations
“…Documented attempts to increase seed yield in RC have in-cluded boron and cobalt applications (Stoltz andWallenhammar, 2014, Tomic et al, 2014) and the use of marker assisted selection and quantitative trait loci analysis in breeding have also been cited as po-tential tools for identifying methods to improve seed yield (Herrmann et al, 2006, Vleugels et al, 2014. Investigations into the molecular basis of seed-setting in tetraploid RC remain ongoing at the time of writing, and may yet facilitate breeders in increasing seed yield and making the seed more aff ordable (Amdahl et al, 2017, Kovi et al, 2017.…”
Section: Cell Size Biomass Accumulation and Agronomic Consequencementioning
confidence: 99%